Feasibility of identifying out of care HIV-positive patients in a hospital setting and enrolling them in a retention intervention. Issue 2 (4th March 2017) - Davila, Jessica A.; Hartman, Christine; Cully, Jeffrey; Stanley, Melinda; Amico, K. Rivet; Soriano, Elizabeth; Minick, Sophie; May, Sarah B.; Giordano, Thomas P.
Abstract : Background: The hospital setting provides an opportunity to re-engage people living with HIV (PLWH) in HIV care. We developed and implemented a protocol to identify PLWH in a hospital setting. The aim of the current study was to report on our strategy to recruit hospitalized HIV patients into an intervention study, and to report on lessons learned for future studies. Methods: Our protocol was developed based on experience of our research staff in recruiting HIV patients as well as clinical input from providers and administrators on delivering care in hospitalized settings. We identified hospitalized PLWH between 2010 and 2013 who were potentially eligible for an intervention study. Patients were identified by review of electronic medical records and clinician referral, followed by in-person screening to confirm eligibility. We examined factors related to identifying and enrolling hospitalized patients, and documented lessons learned. Results: Key strategies included systematic medical record review followed by in-person screening, collaboration with staff, and flexibility in recruitment logistics. We identified 1801 PLWH hospitalized during the 3-year study period. Eighty-four percent ( n = 1514) met the met the inclusion criteria based on medical record review. Of these, 48% ( n = 733) were ineligible. Among eligible patients, 59% ( n = 460) were enrolled. Only 3% ( n = 23) of eligible patients declined; 84% ( n = 321) were not enrolled because they were discharged before enrollment. Lessons learned included (1) needing to identify patients and deliver the intervention before hospital discharge, (2) limiting the complexity of the intervention, and (3) having research staff available on weekends and after hours. Conclusions: Targeted recruitment of hospitalized populations is a feasible and productive approach for finding and engaging PLWH who are newly diagnosed or out of routine care.